Cutaneous Components Leading to Pruritus, Pain, and Neurosensitivity in Atopic Dermatitis: A Narrative Review - Sonja Ständer; Thomas Luger; Brian Kim; Ethan Lerner; Martin Metz; Roni Adiri; Juliana M. Canosa; Amy Cha; Gil Yosipovitch (Adis, Springer Healthcare, 2024)
Abstract Atopic dermatitis (AD) is a chronic, relapsing immunoinflammatory skin condition characterized by sensations such as pruritis, pain, and neuronal hypersensitivity. The mechanisms underlying these sensations are multifactorial and involve complex crosstalk among several cutaneous components. This review explores the role these components play in the pathophysiology of atopic dermatitis. In the skin intercellular spaces, sensory nerves interact with keratinocytes and immune cells via myriad mediators and receptors. These interactions generate action potentials that transmit pruritis and pain signals from the peripheral nervous system to the brain. Keratinocytes, the most abundant cell type in the epidermis, are key effector cells, triggering crosstalk with immune cells and sensory neurons to elicit pruritis, pain, and inflammation. Filaggrin expression by keratinocytes is reduced in atopic dermatitis, causing a weakened skin barrier and elevated skin pH. Fibroblasts are the main cell type in the dermis and, in atopic dermatitis, appear to reduce keratinocyte differentiation, further weakening the skin barrier. Fibroblasts and mast cells promote inflammation while dermal dendritic cells appear to attenuate inflammation. Inflammatory cytokines and chemokines play a major role in AD pathogenesis. Type 2 immune responses typically generate pruritis, and the type 1 and type 3 responses generate pain. Type 2 responses and increased skin pH contribute to barrier dysfunction and promote dysbiosis of the skin microbiome, causing the proliferation of Staphyloccocus aureus. In conclusion, understanding the dynamic interactions between cutaneous components in AD could drive the development of therapies to improve the quality of life for patients with AD.